Hyperoside Ameliorates Diabetic Retinopathy via Anti-Oxidation, Inhibiting Cell Damage and Apoptosis Induced by High Glucose - Wu, Wei; Xie, Zhaolu; Zhang, Qing; Ma, Yunqi; Bi, Xiaoting; Yang, Xue; Li, Bin; Chen, Jianhong (Frontiers in Pharmacology, 2020)
Background: Hyperoside (Hyp) is a flavonoid substance extracted from plants, which has the functions of anti-cancer, anti-inflammatory and anti-oxidation. In the previous study, we found that Hyp reduced the injury of rat retinal vascular endothelial cells (RVECs) induced by H2O2. Method: In the present research, we evaluated the protective effect of Hyp on the pathological damage of retina caused by high glucose of diabetes mellitus (DM) in in vitro and in vivo experiments. The effect of Hyp on cell viability, oxidative stress level and apoptosis of RVECs was assessed. Results: Hyp significantly reduced the of RVECs damage, oxidative stress level and cell apoptosis induced by high glucose in vitro. In DM model rats, Hyp treatment could significantly reduce blood glucose levels and the pathological damage of retina caused by DM, and increase the proliferation of RVECs while exerting the inhibition on apoptotic activity. Furthermore, Hyp treatment decreased the expressions of apoptotic proteins including Caspase 3, Caspase 9, and Bax in RVECs of DM rats, while increased the expression of anti-apoptotic protein Bcl-2. Conclusion: Hyp may have protective effect on diabetes-induced retinopathy by reducing oxidative stress, inhibiting cell damage and apoptosis induced by high glucose.